Cartografia escolar e mapeamento participativo no ensino de Geografia: práticas pedagógicas no ensino fundamental - Negrini, Laís Regina (2024)
Cartography, a science that analyzes the distribution of spatial phenomena, intertwines with Geography and Education to give rise to School Cartography. This dissertation explores the potential of this area in Middle School education, aiming to propose a participatory mapping to assist in the Cartographic Literacy of students at the Professora Edna May Cardoso State School (CEPEMC), motivating the understanding of the lived space. The present research was structured into three stages: The first refers to Workshops for Cartographic Literacy, based on Simielli (1999) and Rizzatti (2016, 2018, 2022), proposing theoretical and practical activities for students to master cartographic concepts. The second stage involves the construction of a participatory mapping, collecting data in the field and validating them in the classroom. Finally, the third stage involves the application of the SWOT Matrix, which assessed the scenario of this research in terms of strengths, weaknesses, opportunities, and threats. Regarding the results, students demonstrate gradual improvement in their mastery of cartographic concepts throughout the activities, with a highlight on orientation. Despite the overall progress, the notions of cartographic alphabet and scale still presented a certain degree of difficulty for students, thus highlighting some of the challenges in teaching this subject. During the creation of the participatory map, in the fieldwork stage, Class X collected 56 points and Class Y 70 points. In both classes, the majority of points were related to improper waste disposal, lack of basic sanitation, and poor urban infrastructure. Class Y had a greater diversity of identified socio-environmental problems, such as dengue risk and flood-prone areas. During this process, students demonstrated cartographic literacy skills, showing greater evolution mainly in relation to the layout of the legend on the map. Cartographic literacy was evident as students identified and discussed socio-environmental problems around the school. The SWOT Matrix revealed that the main strengths lay in the interaction of School Cartography with Place-based Education practiced actively with ICTs. Weaknesses focused on risks related to the applicability and efficiency of activities. Opportunities stood out in the context of the school space, revealing the importance of interaction between Higher Education and Basic Education. Threats highlighted external constraints, including structural and technological aspects, as well as the implementation context. Geotechnologies are a strength when used properly but can also become a weakness if not employed with mastery. The didactic sequence and participatory mapping provided more meaningful and contextualized learning. The research demonstrated a positive impact on School Cartography Education through a well-structured methodology and consistent results. The study offers valuable insights for improving pedagogical practices and fostering active and engaged citizenship.